Double Feature: Carcinoma and Sarcoma Present in a Single Breast Tumor - Catherine M. Stefaniuk; Timothy Jones (Case Reports in Oncological Medicine)
Introduction. Primary breast sarcomas (PBSs) are rare nonepithelial breast tumors compromised of mesenchymal mammary tissue. Although its rare nature has made the best mode of PBS treatment difficult to determine, it seems better to treat it more like a sarcoma creating clear negative margins verses breast carcinoma utilizing lumpectomy, partial mastectomy, and total mastectomy. Case. A 47-year-old obese Caucasian postmenopausal female G2P2 presents with a breast lump demonstrating a histological sample with a biphasic pattern consistent with both ductal carcinoma containing typical malignant epithelial cells and sarcomatous differentiation of carcinosarcoma. Conclusion. Carcinosarcoma is a rare breast malignancy. Sarcomas of the breast tend to be negative for estrogen receptor and lack known risk factors. Current recommended treatment is to treat breast sarcomas like other soft tissue sarcomas by performing wide local excision instead of partial mastectomy. Antiestrogens and other chemotherapeutic agents typically used in breast epithelial malignancies are not recommended since these sarcomas tend to be negative with these receptors.